1990
DOI: 10.1037/1040-3590.2.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Refinements in the assessment of dementia-related behaviors: Factor structure of the memory and behavior problem checklist.

Abstract: This study explored the factor structure of Zarit's Memory and Behavior Problem Checklist (MBPC), a 29-item inventory that samples negative behavior changes associated with dementia (e.g., incontinence and destroying property). Family caregivers for 185 progressive-dementia patients provided information on their affected relatives. A principal-components factor analysis with an oblique (nonorthogonal) rotation produced an 8-factor solution that accounted for 62.9% of the variance. A second-order factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…A number of statistically signi®cant dierences and dierences tending to signi®cance emerged on analysis. By dividing family members according to distress level (low 1±58, moderate 59±87, high burden 88±145) consequent to patients' cognitive and behavioural disorders, assessed through the Memory and Behavior Problems Checklist and Caregiver Burden (Dura et al, 1990) proposed by Rankin et al (1992), 35 supporters fell into the low and 25 into the moderate burden category, but no supporter reached a high burden score.…”
Section: Resultsmentioning
confidence: 99%
“…A number of statistically signi®cant dierences and dierences tending to signi®cance emerged on analysis. By dividing family members according to distress level (low 1±58, moderate 59±87, high burden 88±145) consequent to patients' cognitive and behavioural disorders, assessed through the Memory and Behavior Problems Checklist and Caregiver Burden (Dura et al, 1990) proposed by Rankin et al (1992), 35 supporters fell into the low and 25 into the moderate burden category, but no supporter reached a high burden score.…”
Section: Resultsmentioning
confidence: 99%
“…However, significant inconsistencies across previous studies are evident, both in terms of item content and resulting factor structures. Factor structures with as few as three (Fuh et al, 1999;Teri et al, 1992) and as many as eight (Dura et al, 1990) different factors have been reported.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Exploratory factor analyses of the RMBPC and similar measures of memory and behavior problems have indicated that multiple dimensions underlie these measures (Dura, Bornstein, & Kiecolt-Glaser, 1990;Fuh, Liu, Wang, Wang, & Liu, 1999;McCarty et al, 2000;Teri et al, 1992). In general, memory-related problems have been found to cluster on distinct factors that are largely independent from emotional difficulties and other behavior problems.…”
mentioning
confidence: 99%
See 2 more Smart Citations